# What is an algebraic formula?

Mathematics is a subject with a vast scope of the study. It is divided into different branches like arithmetic, geometry, algebra, etc. As our level of study develops students get introduced to all these branches. Algebra is a branch of mathematics that is approached at the elementary level. In algebra, equations are expressed in terms of coefficients and variables where variables are unknown quantities. These expressions are solved with some given formulas to reach a solution.

### Algebraic expression

An algebraic expression is an equation made up of terms consisting combination of coefficients, variables, and constants. The expressions are presented in the form of mathematical operations like addition, subtraction, multiplication, and division.

### Components of an algebraic expression

**Coefficient:**Coefficients are the fixed numerical values attached to the variable (unknown number). For example in the algebraic expression 5x^{2 }+ 2, 5 is the coefficient of x^{2}.**Variable:**Variables are the unknown values that are present in an algebraic expression. For example in 4y – 1, y is the variable.**Constant:**Constants are the fixed numbers present in the expression. They are not combined with any variable. For example in the expression 5x + 2, +2 is the constant.

### Algebraic formula

Algebraic formulas are the combination of numbers and letters to form an equation or formula. In an algebraic formula, numbers are fixed or constant with their known values. And, the letters represent the unknown values. The below table consists of the important algebraic formulae. In the table letters like a,b,c,m,n, etc represents the unknown quantities of the equation.

Algebraic formulae |
---|

(a + b)^{2 }= a^{2 }+ b^{2 }+ 2ab |

(a – b)^{2 }= a^{2 }+ b^{2 }– 2ab |

a^{2 }– b^{2 }= (a + b)(a – b) |

a a |

a + b = (a + b)(a^{2 }– ab + b^{2}) = (a + b)^{3 }– 3ab(a + b) |

a – b = (a – b)(a^{2 }+ ab + b^{2}) = (a – b)^{3 }+ 3ab(a – b) |

2(a^{2 }+ b^{2}) = (a + b)^{2 }+ (a – b)^{2} |

(a + b)^{2 }– (a – b)^{2 }= 4ab |

a^{4 }+ b^{4 }= (a + b)(a – b)[(a + b)^{2 }– 2ab] |

(a + b + c)^{2 }= a^{2 }+ b^{2 }+ c^{2 }+ 2ab + 2bc + 2ca |

(a – b – c)^{2 }= a^{2 }+ b^{2 }+ c^{2 }– 2ab + 2bc – 2ca |

a^{3 }+ b^{3 }+ c^{3 }– 3abc = (a + b + c)(a^{2 }+ b^{2 }+ c^{2 }– ab – bc – ca) |

a^{4 }+ a^{2 }+ 1 = (a^{2 }+ a + 1)(a^{2 }– a + 1) |

a – b = (a^{4 }+ b^{4})(a^{2 }+ b^{2})(a + b)(a – b) |

a^{m} × a^{n} = a^{(m + n)} |

(a^{m})^{n }= a^{m x n} |

### Sample Problems

**Question 1: Solve the equation (a + b + c)(a + b + c).**

**Solution:**

Given expression, (a + b + c)(a + b + c),

now,

= (a + b + c)(a + b + c)

= (a + b + c)

^{2}By the algebraic formula

= (a + b + c)

^{2 }= a^{2 }+ b^{2 }+ c^{2 }+ 2ab + 2bc + 2ca

**Question 2: Expand a ^{3 }– b^{3}.**

**Solution:**

= a

^{3 }– b^{3}= (a – b)(a

^{2 }+ ab + b^{2})

**Question 3: Multiply (x – y)(3x + 5y)**

**Solution:**

= x(3x + 5y) – y(3x + 5y)

= 3x

^{2 }+ 5xy – 3yx – 5y^{2}= 3x

^{2 }+ 2xy – 5y^{2}

**Question 4: Simplify (y ^{3 }– 2y^{2 }+ 3y – 1)(3y^{5 }– 7y^{3 }+ 2y^{2 }– y + 4)**

**Solution:**

= (y

^{3 }– 2y^{2 }+ 3y – 1)(3y^{5 }– 7y^{3 }+ 2y^{2 }– y + 4)= 3y

^{8 }– 7y^{6 }+ 2y^{5 }– y^{4 }+ 4y^{3 }– 6y^{7 }+ 14y^{2 }– 4y^{4 }+ 2y^{3 }– 8y^{2 }+ 9y^{6 }– 21y^{4 }+ 6y^{3 }– 3y^{2 }+ 12y – 3y^{5 }+ 7y^{3 }– 2y^{2 }+ y – 4Simplifying the like terms,

= 3y

^{8 }– 6y^{7 }+ 2y^{6 }+ 13y^{5 }– 26y^{4 }+ 19y^{3 }– 13y^{2 }+ 13y – 4.

## Please

Loginto comment...